Dereplication and quantification of the ethanol extract of Miconia albicans (Melastomaceae) by HPLC-DAD-ESI-/MS/MS, and assessment of its anti-hyperalgesic and anti-inflammatory profiles in a mice arthritis-like model: Evidence for involvement of TNF-α, IL-1β and IL-6. (10th August 2020) - Quintans-Júnior, Lucindo J.; Gandhi, Sathiyabama R.; Passos, Fabiolla R.Santos; Heimfarth, Luana; Pereira, Erik W.Menezes; Monteiro, Brenda S.; dos Santos, Katielen Silvana; Duarte, Marcelo Cavalcante; Abreu, Lucas Silva; Nascimento, Yuri M.; Tavares, Josean F.; Silva, Marcelo S.; et al.
Abstract: Ethnopharmacological relevance: Miconia albicans (Sw) Triana (Melastomataceae), a medicinal plant widely used by practitioners of folk medicine in the northeast of Brazil, has been used to treat chronic inflammatory disorders, such as rheumatoid arthritis (RA) and other joint conditions. Oddly, there is little research on the species. Aim of the study: We aimed to evaluate the anti-arthritic and anti-inflammatory profile of the ethanolic leaf extract of M. albicans (EEMA), as well as to perform dereplication and quantification by HPLC-DAD-ESI-/MS/MS. Materials and methods: The compounds present in the extracts were identified by HPLC-DAD-ESI-MS/MS. The possible anti-inflammatory effect of EEMA (50 and 100 mg/kg, p.o) was evaluated using the pleurisy model induced by carrageenan and its action on IL-1β and TNF-α levels was also evaluated. The RA model was induced through the intra-articular injection of complete Freund's adjuvant (CFA). Results: HPLC-DAD-ESI-MS/MS analysis identified 23 compounds, with glycoside flavonoids mainly derived from quercetin, and rutin being the main compounds. EEMA significantly reduced (p < 0.001) leukocyte migration in the pleurisy model and reduced TNF-α and IL-1β levels in pleural lavage (p < 0.001). In the CFA animal model, EEMA significantly reduced the nociceptive and hyperalgesic behaviors demonstrated by the rearing test (p < 0.01 or p < 0.05) and decreased mechanical hyperalgesia (p < 0.001). EEMA produced a significant improvement in mobility in the open-field test (only at the higher dose, p < 0.05). EEMA significantly (p < 0.01) increased hindpaw grip strength. The diameter of CFA-induced ipsilateral knee edema was significantly reduced (p < 0.001) by EEMA, which was related to reduced levels of IL-6 and TNF-α in the joint knee (p < 0.01). No indication of hepatic injury after chronic treatment was found. Conclusion: Taken together, these results contribute to the chemical and pharmacological knowledge of M. albicans and demonstrated that this medicinal plant appears to be able to mitigate deleterious symptoms of RA, which supports its use in folk medicine. Graphical abstract: Image 1 Highlights: Miconia albicans a medicinal plant used in folk medicine to treat chronic inflammatory disorders, but is little studied. Ethanol extract of M. albicans (EEMA) is rich in polyphenolic compounds such as flavonoids. EEMA strongly mitigate the painful behavior in experimental arthritis models. EEMA modulate pro-inflammatory cytokines level, such as TNF-α and IL-1β. EEMA produces anti-arthritic profile by inhibition of IL-6 and TNF-α.